Evaluation of decision to delivery time interval and its effect on feto-maternal outcomes and associated factors in category-1 emergency caesarean section deliveries: prospective cohort study - Mamaru Mollalign Temesgen; Amare Hailekirose Gebregzi; Habtamu Getinet Kasahun; Seid Adem Ahmed; Yophtahe Berhe Woldegerima (BMC, 2020)
Abstract Background Category-1 emergency caesarean section delivery is the commonly performed surgical procedure in pregnant women associated with significant mortality and morbidity both in the mother and fetus. The decision to delivery time interval is recommended to be less than 30 min by the Royal College of Obstetricians and Gynecologists as well as the American College of Obstetricians and Gynecologists. This study was designed to evaluate the decision to delivery time interval and its effect on feto-maternal outcomes and the associated factors during category-1 emergency caesarean section deliveries. Method A prospective observational cohort study was conducted from March to May 2018 at the University of Gondar Comprehensive Specialized Hospital obstetrics Operation Theater and postnatal ward. A total of 163 clients who were undergone category-1 emergency caesarean section were included in this study. Statistical analysis was performed using SPSS version 20 (IBM Corporate). Bivariate and multivariate logistic regression with a 95% confidence interval was used to determine the association of decision to delivery time interval with predictor variables and feto-maternal outcomes. Results Only 19.6% of women had a decision to delivery time interval below 30 min. The average decision to delivery time interval was 42 ± 21.4 min, the average time from the decision of category-1 emergency caesarean section arrival to the operation theater was 21.58 ± 19.76 min and from theater to delivery of anesthesia was 11.5 ± 3.6 min. Factors that were associated with prolonged decision to delivery time interval were: time taken to collect surgical materials (AOR = 13.76, CI = 1.12-168.7), time taken from decision and arrival to the operation theater (AOR = 0.75, CI = 0.17-3.25) and time taken from arrival at the operation theater to the immediate start of skin incision (AOR = 0.43, CI = 0.28-0.65). Conclusion Delivery was not achieved within the recommended time interval in the majority of category-1 emergency caesarean sections. The average decision to delivery time interval was longer than the recommended time but it did not affect feto-maternal outcomes.